The effectiveness of interpretation board at Heritage Site in Bandar Hilir Melaka / Nik Nurul Aizah Nik Abdul Rahman , Nurul Azwa Ahmad Kamal and Wan Farah Wan Samsudin - Nik Abdul Rahman, Nik Nurul Aizah; Ahmad Kamal, Nurul Azwa; Wan Samsudin, Wan Farah (Faculty of Hotel and Tourism Management, 2015)
This research was conducted in order to study the effectiveness of interpretation board at heritage sites in Bandar Hilir, Melaka. The purpose was to examine the relationship between three factors which were Attraction Power that provide impact to the effectiveness of interpretation board at Bandar Hilir, Melaka. Assessment on appropriateness of the design and content of interpretation board in enriching visitors' experience at site were examined. For this research, 381 tourists who visit heritage sites at Bandar Hilir, Melaka were chosen as respondents. All data collected through questionnaire were analyzed systematically by using Statistical Package for Social Science (SPSS).